Dataset regarding the mechanical characterization of sedimentary rocks derived from Svalbard for possible use in local road constructions - Diego Maria Barbieri; Jean-Gabriel Dorval; Baowen Lou; Hao Chen; Benan Shu; Fusong Wang; Inge Hoff (Data in Brief, 2021)
The dataset deals with the mechanical characterization of sedimentary rocks collected along the banks of Longyear river in proximity of Longyearbyen (Svalbard) at the junction of Bolterdalen and Adventdalen valleys. As the rocks represent possible local construction materials that can be employed in the new road infrastructures located in the Svalbard archipelago, three types of laboratory investigations were performed for mechanical characterization: Los Angeles tests, micro-Deval tests and repeated load triaxial tests. The grading curve of the material characterized with the repeated load triaxial tests corresponded to a typical one commonly adopted in Norway for road base layer (0–31.5 mm). The dataset offers a thorough overview of the mechanical properties relevant for road constructions and the dataset can be useful to both contractors and transportation agencies operating in the Svalbard archipelago.